Pengaruh Penambahan Substrat Organik Pada Limbah Klorinasi Pabrik Kertas Terhadap Pembentukan Gas Methan Dan Penurunan Senyawa Klorin - Rahyani Ermawati; Sunardi Sunardi (Balai Besar Kimia dan Kemasan, 1996)
Kraft mill bleaching process is some significant source of chlorinated organic compounds. In this process, wood pulp is bleached using plant specific sequence of chlorination with chlorine and extraction with alkali. The waste water from chlorination of Kraft bleaching contains many toxic compounds that very difficult to be removed by conventional activated sludge treatment. Adding an organic substrate will affect the methanogenesis. The aims of this study are: (1). To remove adsorbable organichalide (AOX) by anaerobic treatment, (2). Toexamine the effect co-substrates to methanogenesis, such as methanol and glucose, (3). To know the effect of sterilization to decrease of AOX. The result is AOX can be removed anaerobically with or without co-substrate.